2015
DOI: 10.1152/ajplung.00366.2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cigarette smoke-induced emphysema in mice using quantitative micro-computed tomography

Abstract: T. Evaluation of cigarette smokeinduced emphysema in mice using quantitative micro-computed tomography. Am J Physiol Lung Cell Mol Physiol 308: L1039-L1045, 2015. First published March 27, 2015 doi:10.1152/ajplung.00366.2014.-Chronic cigarette smoke (CS) exposure provokes variable changes in the lungs, and emphysema is an important feature of chronic obstructive pulmonary disease. The usefulness of micro-computed tomography (CT) to assess emphysema in different mouse models has been investigated, but few stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 27 publications
6
39
0
1
Order By: Relevance
“…One possibility is that residual volume may have increased in the female mice after chronic smoke exposure, corresponding to dynamic hyperinflation in patients with emphysema, which may reflect an increased tendency for remodelled peripheral airways to collapse at low lung volumes. In support of our observations, Sasaki and colleagues showed that female C57BL/6 mice have increased end-expiratory lung volume after 20 weeks of cigarette smoke exposure [16]. Furthermore, total lung capacity was increased in mice exposed to 16 weeks of smoke exposure compared to wild type mice [17].…”
Section: Discussionsupporting
confidence: 83%
“…One possibility is that residual volume may have increased in the female mice after chronic smoke exposure, corresponding to dynamic hyperinflation in patients with emphysema, which may reflect an increased tendency for remodelled peripheral airways to collapse at low lung volumes. In support of our observations, Sasaki and colleagues showed that female C57BL/6 mice have increased end-expiratory lung volume after 20 weeks of cigarette smoke exposure [16]. Furthermore, total lung capacity was increased in mice exposed to 16 weeks of smoke exposure compared to wild type mice [17].…”
Section: Discussionsupporting
confidence: 83%
“…7c). These data suggest that mild emphysema developed at 16 weeks of CS exposure in WT mice as observed in the previous report [31]. On the other hand, we found that CS exposure neither increased the lung volume nor Lm in Aldh2*2 Tg mice (Fig.…”
Section: Resultssupporting
confidence: 91%
“…All lungs were examined by micro-CT scanning followed by euthanasia and the lungs were collected and embedded in paraffin, to examine for digital and histological signs of lung damage and emphysema. Digital readings of the low attenuation area (LAA)%, CT values, and lung volumes were compared between the WT and Aldh2*2 Tg mice as previously described [31].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations